2007
DOI: 10.1002/cphc.200700369
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Influence on the Type of Stabilization of Sulfur Radical Cations in Cyclic Peptides

Abstract: The free-radical chemistry of two oxidized cyclic dipeptides is investigated using time-resolved optical and conductivity detection. Two cyclic dipeptides, cyclo-Gly-L-Met and cyclo-D-Met-L-Met, are synthesized and irradiated with nanosecond pulses of electrons, which initiate the oxidation of the methionine side chains with hydroxyl radicals from the radiolysis of water. The cyclic peptides are taken to be models for the interior of proteins where there are no terminal groups. This opens up the possibility th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 29 publications
(55 reference statements)
2
38
1
Order By: Relevance
“…However, one problem that persisted was the difficulty of determining minor products that had spectral shapes and positions in somewhat different places than those of the major species, yet whose spectral features were still in some sense close to those of the major species [16]. In these cases, it was difficult to determine if the minor species was in fact present, or whether the reference spectra for the major species was not quite correct.…”
Section: Contrasting Multilinear Regression and Factor Analysismentioning
confidence: 96%
See 4 more Smart Citations
“…However, one problem that persisted was the difficulty of determining minor products that had spectral shapes and positions in somewhat different places than those of the major species, yet whose spectral features were still in some sense close to those of the major species [16]. In these cases, it was difficult to determine if the minor species was in fact present, or whether the reference spectra for the major species was not quite correct.…”
Section: Contrasting Multilinear Regression and Factor Analysismentioning
confidence: 96%
“…The reference transient spectra were taken from analogous species (as in [16]), and the results suggested that (S;S) ? , neutral (S;N), and (aS) were likely present in the time range of 10-90 ls following the electron pulse.…”
Section: Application To Pulse Radiolysis Of Cyclic Dipeptidesmentioning
confidence: 99%
See 3 more Smart Citations